The Day After Tomorrow : A Handbook on the Future of Economic Policy in the Developing World - Editors Giugale, Marcelo and Canuto, Otaviano (Washington World Bank, 2010)
In this title some 40 development economists, most of them from the World Bank's poverty reduction and economic management network, an epicenter of the profession, tell us what they see on the horizon of their technical disciplines and of their geographic areas of specialization. Following the 2008-09 global financial crises, much economic policy is up for reexamination. This synthesis picks from each chapter what is new, what is likely to change, and what will be different in the future
Include Index
Keywords: Poverty -- Developing countries -- International economic relations